Beneficial effects of eugenol supplementation on gut microbiota and hepatic steatosis in high-fat-fed mice. Issue 6 (1st March 2022) - Rodrigues, Marina; Bertoncini-Silva, Caroline; Joaquim, Anderson Gregorio; Machado, Cássia Dias; Ramalho, Leandra Náira Zambelli; Carlos, Daniela; Fassini, Priscila Giacomo; Suen, Vivian Marques Miguel
Abstract : Due to the increase in the prevalence of obesity, new therapies have emerged and eugenol has been shown to be beneficial in metabolic changes and gut microbiota. Abstract : Due to the increase in the prevalence of obesity, new therapies have emerged and eugenol has been shown to be beneficial in metabolic changes and gut microbiota. This study aimed to investigate the effects of eugenol on gut microbiota, hepatic lipid accumulation, body weight, adipose tissue weight, lipid and glycemic profile in mice fed a high-fat diet. Forty C57BL/6 male mice were divided into standard diet (SD), high-fat diet (HFD), standard diet with eugenol (SDE) and high-fat diet with eugenol (HFDE). The dose used of eugenol was 500 mg kg −1 for 8 weeks. Eugenol did not prevent weight gain, but it was effective in preventing hepatic lipid accumulation evidenced by the presence of fat droplets in the HFD group and absence in the HFDE group. An improvement in the gut microbiota profile was observed, proved by an increase in the Actinobacteria phylum in the treated groups and a reduction of Proteobacteria phylum in the HFDE group. Despite not preventing weight gain, eugenol appeared to have a protective effect on hepatic lipid accumulation and beneficially modulate the gut microbiota in mice fed with HFD.